Supramolecular Organic Framework with Multidimensional Storage Spaces for Ultrahigh-Capacity Iodine Capture from Seawater - Lijuan Feng; Jun Zhang; Jiacheng Zhang; Xuewen Cao; Zhanhu Guo; Yihui Yuan; Ning Wang (Research)
Given the important role of iodine resources in chemical industry application and the scarcity of geogenic iodine resources, sustainable access to iodine resources has become increasingly crucial. Seawater is the largest iodine reservoir on Earth, but efficient chemical methods for recovering iodine from seawater are still lacking. Concurrently, the remediation of radioactive iodine pollution in seawater, caused by nuclear accident, remains a great challenge. Supramolecular organic frameworks (SOFs) are considered promising candidates for the recovery of aqueous iodine. However, currently available SOF adsorbents lack sufficient iodine storage space, resulting in low iodine adsorption capacity. Herein, we developed a 3-dimensional (3D) SOF, named SOF-HTNI, via the self-assembly of 2 adjustable compounds, including the internal amine bond-rotatable 5-(bis(4-carboxybenzyl)amino)isophthalic acid (HT) and the configuration-transformable 4,4′-[1,4-phenylenedi-(1E)-2,1-ethenediyl]bis-pyridine (NI), for highly efficient iodine recovery from seawater. Due to the rigid support and the formation of hydrogen bonds and π–π stacking interactions between the compounds, interconnected 1D channels and 2D interlayer nanospaces are constructed within SOF-HTNI, providing abundant flexible spaces for iodine storage. By combining the charge interaction of the amine and pyridyl groups from the compounds with the binding ability of aromatic rings, SOF-HTNI achieves impressive iodine adsorption capacities of 436.56 mg g−1 to iodide and 5.03 g g−1 to triiodide. Notably, SOF-HTNI realizes a high iodine capture capacity of 46 mg g−1 in natural seawater, 40 times greater than that of seaweed. These findings make SOF-HTNI a highly promising material for iodine pollution treatment and iodine resource recovery in seawater.